Eldecalcitol effectively prevents alveolar bone loss by partially improving Th17/Treg cell balance in diabetes-associated periodontitis - Gao, Ruihan; Zhang, Weidong; Jiang, Yujun; Zhai, Junzhe; Yu, Jian; Liu, Hongrui; Li, Minqi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Diabetes-associated periodontitis (DPD) is an inflammatory and destructive disease of periodontal tissues in the diabetic population. The disease is manifested as more severe periodontal destruction and is more difficult to treat when compared with periodontitis (PD). Eldecalcitol (ELD) is a novel active vitamin D3 analog; however, little clinical evidence is available on its role on improving PD and DPD, and its specific mechanisms remain unclear. In this study, we evaluated the preventative effects of ELD toward PD and DPD and explored its underlying molecular mechanisms. Results: Micro-CT and HE staining showed that the DPD group had higher alveolar bone loss when compared with the PD group. After applying ELD, alveolar bone loss decreased significantly in both PD and DPD groups, and was approximately similar. IHC and TRAP staining also showed that ELD promoted osteoblast activity while inhibiting osteoclasts, and after ELD treatment, the receptor activator of nuclear factor-κB ligand (RANKL) to osteoprotegerin (OPG) ratio decreased. Flow cytometry and qRT-PCR also showed that the systemic Th17/Treg imbalance in PD and DPD groups was partially resolved when animals were supplemented with ELD, while immunofluorescence staining and qRT-PCR data showed the Th17/Treg imbalance was partially resolved in the alveolar bone of both ELD supplemented groups. Western blotting and immunofluorescence staining showed increased p-STAT5 and decreased p-STAT3 levels after ELD application. Conclusion: ELD exerted preventative effects toward PD and DPD by partially rectifying Th17/Treg cell imbalance via STAT3/STAT5 signaling.